Arterial and venous thrombosis with right ventricular thrombus in Crohn’s disease - Shankar, Sujay Halkur; Kumar, Prabhat; Madhusudan, Kumble S. (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Halkur Shankar S, Kumar P, Madhusudan KS. Arterial and venous thrombosis with right ventricular thrombus in Crohn’s disease. Turk J Gastroenterol 2019; 30(12): 1070-1.